THE PORTRAYAL OF MALIGNANT NARCISSM IN THE VILLAIN CHARACTERS OF DISNEY MOVIES - Shabrina Kiranamita; Samanik S.S.,M.Hum (Linguistics and Literature Students' Journal, 2021)
The uncomfortable condition of people to talk about mental illness often leads to its misinterpretation and stereotype. It includes to Malignant Narcissism. Therefore, this research aims to discuss about the portrayal of Malignant Narcissism in the villain characters of Disney Movie, which are the character Jafar in Aladdin movie (2019) and Cinderella’s Step Mother character in Cinderella movie (2015). By using Disney live-action movies as the object, this research aims to find the symptoms of Narcissistic Personality Disorder and Malignant Narcissism in the sufferer through the villain characters, and to find the impacts of the sufferers to their surroundings.This research used descriptive qualitative method typically library research with textual analysis since the data of this research are in the form of sentences and dialogues. The primary data sources are Aladdin (2019) and Cinderella (2015) movies, and the secondary data sources are journals and previous studies. This research used psychology of literature and psychology film as the approaches. In order to answer the research question, the researcher used Narcissistic Personality Disorder and Malignant Narcissism symptoms according to Diagnostic and Statistical Manual of Mental Disorder.The results of this research show that both Jafar character in Aladdin movie and Cinderella’s Step Mother in Cinderella movie suffer Narcissistic Personality Disorder, specifically with the type of Malignant Narcissismbased on the symptoms that identified in both characters.Keywords: Disney movies, narcisstic personality disorder, malignant narcissism